Cucurbitacin B Inhibits Cell Proliferation by Regulating X-Inactive Specific Transcript Expression in Tongue Cancer - Tao, Boqiang; Wang, Dongxu; Yang, Shuo; Liu, Yingkun; Wu, Han; Li, Zhanjun; Chang, Lu; Yang, Zhijing; Liu, Weiwei (Frontiers in Oncology, 2021)
As a natural product, cucurbitacin B (CuB) has anti-tumor effects on various cancers. In this study, RNA sequencing and quantitative PCR were used to analyze the expression of long non-coding RNAs (lncRNA) and X-inactive specific transcript (XIST) in CAL27 and SCC9 tongue squamous cell carcinoma (TSCC) cells after CuB treatment. Moreover, our results showed increased expression of XIST in human tongue cancer CuB treatment reduced XIST expression and inhibited the proliferation of SCC9 cells. Knockdown of XIST inhibited cell proliferation and induced apoptosis in vitro, and inhibited tumor growth in vivo. MicroRNA 29b was found to be a direct target of XIST. The clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein 9 system confirmed the role of XIST knockout in tumor development in vivo. Together, these results suggest that CuB exerts anti-cancer activity by regulating the expression of XIST.